Clonal Mature Adipocyte Production of Proliferative-competent Daughter Cells Requires Lipid Export Prior to Cell Division - Chen, Jie (Korean Society for Stem Cell Research, 2009)
BACKGROUND AND OBJECTIVES: Numerous in vitro observations have been published to show that mature adipocytes may resume proliferation and begin to populate the adipofibroblast fraction or form other cell types. METHODS AND RESULTS: In the present study, we evaluated clonal cultures of mature pig-derived adipocytes as they began to reestablish their ability to divide. The lipid contained within the cytoplasm was either moved to the apical ends of the cell, or large droplets were physically extruded from the cell. In the latter case, we ascertained that the cell lipid droplet was handled in a different manner to that by beef-derived adipocytes as described in other published studies. CONCLUSIONS: Pig-derived adipocytes expel large amounts of lipid directly into the medium environment prior to becoming capable of cell division, rather than retaining all lipids like the beef cells. This difference in lipid handling and trafficking may be a novel mechanism in adipocyte resumption of proliferation.